News sentiment and sovereign credit risk - Cathcart,L; Gotthelf,N; Uhl,M; Yining,S (European Financial Management, 2020)
We explore the impact of media content on sovereign credit risk. Our measure of media tone is extracted from the Thomson Reuters News Analytics database. As a proxy for sovereign credit risk we consider Credit Default Swap (CDS) spreads, which are decomposed into their risk premium and default risk components. We find that media tone explains and predicts CDS returns and is a mixture of noise and information. Its effect on risk premium induce a temporary change in investors’ appetite for credit risk exposure whereas its impact on the default component lead to reassessments of the fundamentals of sovereign economies.